Real-time path planning considering static and dynamic obstacles - Subies Hueso, Josep; Mondal, Sabyasachi; Tsourdos, Antonios (American Institute of Aeronautics and Astronautics (AIAA), 2024)
This paper introduces a real-time path planning strategy that effectively navigates around both static and dynamic obstacles. The approach combines the principles of Generalised Explicit Vector (GENEX) and Inverse Proportional Navigation (IPN), established algorithms in missile guidance known for their advantageous features such as low computation and closedform expressions. Leveraging these attributes, the proposed strategy addresses path planning challenges involving static and dynamic obstacles. The performance of the combined algorithm is assessed through a comprehensive simulation study in both 2D and 3D scenarios, considering multiple static and dynamic obstacles.